Literature as a discursive event or Swiss women in history and on the literary stage - Kondrič Horvat, Vesna (Anali PAZU HD, 2022)
The article deals with the question of why Swiss women were late entrants on the literary scene. We understand literature as a discoursive event-meaning that the destiny of literary works is not decided by their aesthetic value alone, but also by the prevailing discourse, which influences the production and reception of literary works; it decides who is allowed to write, what one is allowed to write, what one can publish and what is prohibited. For Swiss female writers, it was crucial that voting rights on the federal level were gained by women in Switzerland only in 1971. In this article, we introduce works dealing with the history of women in Switzerland and elucidating why female writes were for such a long time absent from the literary scene. The definition of the "Swiss literary style" at the beginning of the 20th century and the handling of works by female authors in literary histories both clarify that literature is a discursive event, from which Swiss female writers were long excluded.
Keywords: female authors; Swiss literature; history; female history; literary history; voting rights